Comparison of Unigram, Bigram, HMM and Brill's POS tagging approaches for some South Asian languages - Hasan, Muhammad Fahim; Naushad UzZaman; Khan, Mumit (BRAC University, 2010)
Includes bibliographical references (page 6-8).